PEREMPUAN DALAM BUADAYA POLITIK PATRIAKHI - Achmad Zahruddin (Fakultas Ilmu Sosial dan Ilmu Politik, 2021)
The condition of parlement thougt that has gradually been canging from traditional thought into the more modern one sometimes result various demands to appear. How the participation in patriarchy culture that have domination one each ather. These demands include the wider people’s participation, in politics. In only rural people are pursuin this wider participation, another ‘marginalized’ group souch as the women’s group, is also showing their desire to get in volve actively in this field. This wider participation is viewed by women of the process to improve their sanity and involvements in polics without exeption or without any segregation. According to the number of female representation in parliament is far from the ideal condition, just 3%-11,5% women regislator from the total seat of regislator in the parliament. Ironically, one side women have 30% quota is realitation of affirmative action, but just 3%-11,5% the women regislator seat in the parliament. Unfortunetelly; the result shows contradiction the female representatives are not quite capable to perform the mandate with maximum 1156% seat from the total seat of the legislator.